An assessment of job satisfaction: A cross-sectional study among orthodontists of Saudi Arabia - Nasser D Alqahtani; Khaled Alshehry; Saad Alateeq; Hammad Alturki; Sahar Albarakati; Moshabab A Asiry; Muhammad S Ahmedani (Wolters Kluwer Medknow Publications, 2018)
AIM OF THE STUDY: The main objective of the present study was to investigate the level of job satisfaction among professional orthodontists in relation to some significant intrinsic and extrinsic factors that generally affect their performance. MATERIALS AND METHODS: A cross-sectional study was conducted among orthodontists working in the Kingdom of Saudi Arabia using an online survey questionnaire through Survey Monkey. A total of 161 responses were received; among those, 57.8% of the respondents were Saudi and 42.2% were non-Saudi. RESULTS: On an overall satisfaction basis, a majority of orthodontists (80.7%) were satisfied with orthodontics as their profession irrespective of their gender. Only 4.4% showed dissatisfaction, whereas the remaining 14.9% were moderately satisfied with orthodontics as a profession. In-depth analysis revealed that a majority of the respondents (56.2%) showed reservations over having ample time for their family life. 52.8% of the respondents strongly agreed that they are assigned significant paperwork. Likewise, 66.5% of the orthodontists showed moderate to dissatisfaction over time adherence by the patients. CONCLUSION: The findings of the present investigations depicted a higher level of passion and commitment among the male and female respondents for the profession in spite of the fact that they do not have adequate time for their personal life. The working efficiency of orthodontists may be significantly enhanced by sparing them from too much paperwork and ensuring that their patients appear on time.